Assessment of Sociodemographic Status, Self-awareness, and Risk Factors Affecting Patients with Prediabetes in Bangladesh: Cross-sectional Study - Sultana, Farhana; Islam, Muhammed Mohibul; Das, Aparajita; Rahman, Md Hasan Shahriar; Pia, Nandita Islam; Mahmud, Md Kayes; Mostaq, Md. Saqline; Saadullah, Saadullah; Hossain, Md. Saddam; Fakir, Saikat; Amin, Mohammad Nurul (UI Scholars Hub, 2024)
Background: Poor glycemic control and high diabetes and prediabetes incidence are influenced by socioeconomic disparity. Raising awareness and ensuring that people with prediabetes are receiving medication, maintaining their glycemic control, and getting the proper care they need despite their socioeconomic situation are crucial in the fight against diabetes. This study aims to assess the sociodemographic status, self-awareness, and risk factors associated with prediabetes in Bangladesh. Methods: A cross-sectional survey was carried out among 500 participants aged >18 years to evaluate and summarize their demographic data, socioeconomic status, and responses to various questionnaires about their conditions related to prediabetes and their awareness of this condition. Results: Analysis of factors revealed that 41% and 39% of the participants had first- and second-degree relatives with diabetes, respectively. Meanwhile, 36% of the participants maintain physical activities, 30% prefer sweetened beverages, and 29% have high blood pressure. The participants were aware of different statements related to diabetes, such as how lifestyle modification and awareness can help people with prediabetes. Conclusions: This study provided insights into the underlying factors related to prediabetes and enabled us to identify the prediabetes conditions unknown to people in Bangladesh.